Molecular Docking Studies on the Anti-viral Effects of Compounds From Kabasura Kudineer on SARS-CoV-2 3CLpro - Vincent, Savariar; Arokiyaraj, Selvaraj; Saravanan, Muthupandian; Dhanraj, Manoj (Frontiers in Molecular Biosciences, 2020)
The COVID-19 has now been declared a global pandemic by the World Health Organization. No approved drug is currently available; therefore, an urgent need has been developed for any antiviral therapy for COVID-19. Main proteases of this novel Coronavirus (SARS-CoV-2) play a critical role in the disease propagation, and hence represent a crucial target for the drug discovery. Herein, we have applied a bioinformatics approach for drug repurposing to identify the possible potent inhibitors of SARS-CoV-2 Main Proteases. In search of the anti-COVID-19 compound, we selected 145 phyto-compounds from KK, a poly-herbal formulation recommended by AYUSH for COVID-19 which are effective against fever, cough, sore throat, shortness of breath (similar to SARS-CoV2-like symptoms). The present study aims to identify molecules from natural products which may inhibit COVID-19 by acting on the main protease (Mpro). Obtained results by molecular docking showed that, Acetoside (-153.06), Luteolin 7 -rutinoside (-134.6) rutin (-133.06), Chebulagic acid (-124.3), Syrigaresinol (-120.03), Acanthoside (-122.21), Violanthin (-114.9), Andrographidine C (-101.8), myricetin (-99.96), Gingerenone -A (-93.9), Tinosporinone (-83.42), Geraniol (-62.87), Nootkatone (-62.4), Asarianin (-79.94) and Gamma sitosterol (-81.94) are main compounds from KK plants which may inhibit COVID-19 giving the better energy score compared to synthetic drugs. Based on the binding energy score, we suggest that these compounds can be tested against Coronavirus and used to develop effective antiviral drugs.